KINERJA KEPALA SEKOLAH SEBAGAI INSTRUCTIONAL LEADER - Herawan, Endang (PEDAGOGIA, 2015)
One of the tasks that must be performed by a school principal is the leader. To achieve quality learning, principals in running leadership should be oriented or focus on learning. Leader learning in performing their duties aimed at aspects of the curriculum, PBM, assessment of learning outcomes, teacher development, creating a conducive environment that allows teachers and guide students can study well. To be able to carry out leadership learning required set of competencies, is to formulate learning objectives, directing and guiding curriculum development , improvement PBM, evaluating the performance of teachers and develop it, build a learning community and continuous improvement and build a community of learners .Keywords: Leadership, Competence, Community.